Anti-Diphtheria Antitoxic Immunity in the Population of Rostov-on-Don and the Rostov Region - E. V. Kovalev; G. G. Kharseeva; S. A. Nenadskay; A. M. Ryabova; E. L. Alutina; I. S. Vorotnykova; G. A. Myroshnichenko; M. M. Shvager; M. Ya. Zanina (Эпидемиология и вакцинопрофилактика, 2019)
The aim of the study was to assess the level of vaccination and the state of tension of diphtheria antitoxic immunity in the population. Materials and methods. The level of inoculation and the state of tension of anti-diphtheria antitoxic immunity were determined for the period 2013–2017 among the population of Rostov-on-Don and the Rostov region (children 3–4 years old (1075 people), teenagers 16–17 years old (1107 people), adults 18 and older (1818 people). Discussion. The vaccination coverage of the child population was 98.5–99.2%, adolescents – 98.8–99.8%, adults – 98.0–98.7%. When assessing the level of anti-diphtheria antitoxic immunity, it was established that the number of seropositive to diphtheria among children was 96.1 ± 0.6% of the examined, adolescents – 98.0 ± 0.4% of the examined, adults – 91.5 ± 0.6% of the examined. The highest indices of the level of antitoxic immunity to diphtheria, assessed by the number of both seropositive and persons with high antitoxin titers (82.3 ± 1.1% of the examined) were found among adolescents. The results of the serological monitoring of anti-diphtheria antitoxic immunity as a whole confirmed the data on the almost complete vaccination coverage of the population and indicated a high level of its tension. Conclusion. Vaccination and timely vaccination against diphtheria ensured a successful diphtheria situation in the region.